Digestive Proteolytic Activity in the Sunn Pest, Eurygaster integriceps - Hosseininaveh, Vahid (University of Wisconsin Library, 2009)

(untitled)
The Sunn pest, Eurygaster integriceps Puton (Heteroptera: Scutelleridae), is one of the most important pests of wheat and causes considerable damage to this valuable crop annually. Digestive proteinase activity of adult insects was investigated using general and specific substrates and inhibitors. Proteolytic activity was low when the common conventional substrates, azoalbumin, azocasein and hemoglobin were used to assay salivary glands and midguts. Using the fluorescent casein substrate (BODIPY FL casein), total proteolytic activity was measured at different pH. Maximum proteolytic activity was detected at pH 7 (100%) and 8(65%) which suggested the presence of serine proteinases in the salivary glands. There was no detectable proteolytic activity in midgut extracts. The inhibitors; PMSF (inhibitor of serine proteinases) and TPCK (a specific chymotrypsin inhibitor) showed greater than 50% inhibitory effect on total proteolytic activity, however, TLCK (specific trypsin inhibitor) and E-64(specific cysteine proteinase inhibitor) did not inhibit total proteolytic activity. Using fluorescent specific substrates for serine and cysteine proteinases (Z-Arg-AMC, Z-Arg-Arg-AMC, Z-Arg-Phe-AMC and Suc-Ala-Ala-Pro-Phe-AMZ) revealed the presence of tryptic and chymotryptic activity in the salivary gland extract. Zymogram analysis under non-reducing SDS-PAGE conditions and using the substrate APNE showed at least 8 tryptic and chymotryptic activity bands in salivary gland extracts. A single high molecular weight band with tryptic activity (165 kDa) was detected using the substrate BApNA in a zymogram analysis uisng native-PAGE. Kinetic studies showed a k(m) value of 0.6 mM for this enzyme against the substrate BApNA .The inhibitor TLCK decreased activity of the trypsin-like enzyme up to 73% and almost completely eliminated the only band related to this proteinase in the zymogram. Soybean Kunitz type trypsin inhibitor showed no effect on proteolytic activity of the trypsin-like serine proteinase. In general, the results revealed the presence of chymotrypsin- and trypsin-like serine proteinases in the salivary gland of E. integriceps, and it seems that the major total proteolytic activity is due to chymotrypsin proteinases.